(untitled) (Research, Society and Development, 2020)
Objective: to verify what are the popular practices used for otalgia and cleaning of the external auditory canal. Methodology: qualitative research conducted by interviewing people known in their cities for having knowledge about popular practices, who recognized at least one practice used for earache; 54 people were interviewed. The applied questionnaire contained socio-demographic issues related to cleaning practices and ear pain. Results: most of the people interviewed (53.70%) are between 40 and 59 years old; 92.59% stated that they use informed practices; the main motivations for the application of the practices are the practicality of doing it, the low cost, as well as the easy access to the products used. The cotton swab was the main object used to clean the external auditory canal; and most practices are administered with heated components. Conclusion: the use of popular practices for ear pain is widespread in society, verifying that their use occurs in high frequency compared to the drugs used in current medicine